Development of Indonesian Language Digital Literacy E-Module and Its Effectiveness In Improving Reading Comprehension Skills Of Fifth Grade Students at SD Negeri 3 Randulawang - RIA YULI PERMATASARI; Sri Margiyati (Universitas PGRI Semarang, 2025)
This study focuses on the design and testing of the effectiveness level of an Indonesian language digital literacy e-module intended for fifth-grade elementary school students. The approach applied is Research and Development (R&D) by adopting the ADDIE model framework, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The initial analysis phase was carried out through a needs assessment involving two teachers and twenty students at SD Negeri 3 Randulawang. The final product produced is an interactive e-module based on the Canva platform that comprehensively integrates reading comprehension content, creative writing activities, and basic digital literacy tasks. Product effectiveness testing used a one-group pretest-posttest design. Primary data collection was conducted using a literacy test instrument that had previously undergone expert validation. Statistical analysis with the paired sample t-test proved a significant increase (t(19) = 6.72, p < 0.001), supported by an average N-Gain score of 0.52, which falls into the medium improvement category. These findings confirm that the designed e-module is effective in developing students' literacy competencies. The research conclusion affirms that integrating technological elements into contextually designed literacy teaching materials can be an innovative alternative to strengthen the School Literacy Movement (GLS). As a follow-up, it is recommended to conduct trials with a broader scope using a control group design and to develop content in other dimensions of digital literacy.